Transitional neurosurgery: is a new sub-specialty? - Sosa, Fidel; Rodriguez, Facundo; Diaz, Agustín; Argañaraz, Romina; Lambre, Jorge; Liñares, Juan Manuel (Revista Argentina de Neurocirugía, 2020)
Introduction: The transition process of a patient from the pediatric stage to an adult is a dynamic, complex and planned process, which includes the transfer itself from a pediatric institution to an adult. The objective of this paper is to describe situations and difficulties that exist in the current public health of the process of transition to adult care of pediatric patients with chronic neurosurgical pathology with lifelong follow-up or of adult patients with congenital pathology. For this purpose, communication, social and economic factors must be considered. The increased children and adolescents’ survivors with chronic pathologies, the lack formal agreements between Health Institutions plus the lack of a multidisciplinary approach in these cases, are the most important issues to consider. Methods: Observational, cross-sectional and retrospective study with illustrative cases of patients with transitional neurosurgical pathology from January 1, 2017 to December 31, 2018. In total, 47 patients with an age range between 17 and 42 years were observed. Results: About of 47 patients were observed, we divided them into 2 groups: GROUP 1: adult patients operated on at pediatric age who require chronic follow-up of their origin pathology; and GROUP 2: adult patients with congenital pathology. In GROUP 1, we observed 38 patients (24 male and 14 female) of whom 24 were performed a neurosurgery and 14 were not. Within this group, 63% (n = 29) of the patients presented hydrocephalus as their base pathology for follow-up. In GROUP 2, we observed 9 patients (2 male and 7 female) of whom 7 were operated and 2 were not operated. All patients in this last group presented spinal dysraphism as their basic diagnosis. Discussion: We find in the literature numerous studies of the transition process in the medical field, but very few of them in the neurosurgical field. Taking into account that many of the transitional pathologies are difficult to manage and, in many cases can compromise the life of the patient if they are not detected and treated in a timely manner, we consider it essential to have an adequate transition process in charge of this new subspecialty proposal which we cover. It is essential to have a summary of medical history, to know the new place to be followed and that doctors are used to solve transitional neurosurgical pathology. Currently, there are no formal inter-institutional agreements for the monitoring and care of these patients. Conclusion: A planned transition for the well-care health of young patients with special health care needs must be accomplished. Currently, there are no formal institutional agreements for the monitoring and care of these patients. We believe that there is a group of patients who would benefit from the creation of a new neurosurgical sub-specialty: the transitional neurosurgery. It should be carried out in high complexity general hospitals, where neurosurgeons with pediatric training could be part of a general neurosurgery department.